Change of Mandibular Position during Two-Phase Orthodontic Treatment of Skeletal Class II in the Chinese Population - Rhonda Nga Yi Cheung; Urban Hägg; Ricky Wing Kit Wong; Chongshan Liao; Yanqi Yang (The Scientific World Journal)
The aim of this study was to evaluate the change in mandibular position during a two-phase orthodontic treatment of skeletal Class II malocclusion. Thirty consecutively treated Chinese male adolescents who had undergone two-phase treatment with Herbst appliance and fixed appliance and fulfilled the specific selection criteria were sampled. Cephalograms taken at T0 (before treatment), T1 (at the end of functional appliance treatment), and T2 (at the end of fixed appliance treatment) were analyzed. The change in sagittal positioning of the mandible was 6.8±3.44 mm in phase I (T0-T1), 0.4±2.79 mm in phase II (T1-T2), and 7.2±4.61 mm in total. The mandible came forward in 100% of the patients at T1. In phase II, it came forward in one-third (positive group) remained unchanged in one-third (stable group) and went backward in one-third (negative group) of the patients. At T2, it came forward twice as much in the positive group compared to the negative group. Mandibular length was significantly increased in 100% of the patients in both phases. In conclusion, during the treatment with functional appliance, the mandibular prognathism increases in all patients, whereas during the treatment with fixed appliance there is no significant change in mandibular prognathism.